Giria et Argot, Dictionnaire d'argot bresilien (giria) - argot francais : plus particulierement des villes de Sao Paulo et Rio de Janeiro dans les annees 1960 et 1970 - Audubert, Albert (Beihefte zur Zeitschrift für romanische Philologie ;, 1996)
Main description: The dictionary explores Brazil's langue populaire and argot (gria), concentrating on the world of crime and crime-fighting and listing notably the vocabulary employed in the metropolises of So Paulo and Rio de Janeiro. These terms are paired off with definitions in French and equivalents taken from franais populaire and French argot. This approach is also applied to the closely interwoven professional and group jargons encountered in a variety of social sectors such as school, factory labor, art, information, games and sports (football), as well as the language of young people, who in Brazil constitute a well-defined social category of their own.